Algae and Sustainable Technologies: Bioenergy, Nanotechnology and Green Chemistry - Upadhyay, Atul Kumar; Singh, D. P. (CRC Press, 2021)
Algal and Sustainable Technologies: Bioenergy, Nanotechnology and Green Chemistry is an interdisciplinary overview of the world's major problems: water scarcity, a clean environment and energy, and their sustenance using microalgae. It comprehensively presents the way to tackle the socioeconomic issues including food, feed, fuel, medicine and health, and also details the untapped potential of microalgae in environmental management, bioenergy solutions and the sustainable synthesis of pharmaceutical and nutraceutical products. The book emphasizes the potential success of algae as feedstocks for the future and provides up-to-date information and a sustainable and recreational outlook towards the degrading environment and energy crisis. Applicability of fast emerging algae-based nanotechnology in the bioremediation and production of nanoparticles (AuNPs, AgNPs etc.) is beautifully described along with the latest research and findings. Key Features: The 'waste to best to income' strategies are the main concern of the book and as well as solutions to the problems of pollution, energy and income. Elucidates the sustainable phycoremediation and nanoparticle functions as low-cost approaches for various ecosystem services. Information regarding pharmaceuticals, nutraceuticals and other algae-based value-added products are comprehensively discussed. Knowledge resources, the latest research, findings and prospects are presented in an accessible manner for researchers, students, eminent scientists, entrepreneurs, professionals and policy makers.